1999
DOI: 10.1029/1998gb900002
|View full text |Cite
|
Sign up to set email alerts
|

Enigmatic stable isotope dynamics of deep peat methane

Abstract: Abstract. The carbon and hydrogen stable isotope ratios of methane and carbon dioxide from Ellergower Moss, a raised peat bog in SW Scotland, were measured to characterize the isotopic composition of peatland gas flux that is not subject to near-surface bacterial oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 43 publications
9
37
1
Order By: Relevance
“…Major effects on δ 13 C in CO 2 should thus be due to methanogenic activity (Whiticar, 1999). A residual enrichment of 13 C in CO 2 as observed in this study is consistent with prior investigations (Hornibrook et al, 2000a;Lansdown et al, 1992;Waldron et al, 1999) and is typical for methanogenic environments, due to strong fractionation during methanogenesis (Conrad, 2005;Whiticar, 1999). Therefore, it was frequently found that δ 13 C CO 2 does Fig.…”
Section: Respiration and Methanogenesissupporting
confidence: 78%
See 2 more Smart Citations
“…Major effects on δ 13 C in CO 2 should thus be due to methanogenic activity (Whiticar, 1999). A residual enrichment of 13 C in CO 2 as observed in this study is consistent with prior investigations (Hornibrook et al, 2000a;Lansdown et al, 1992;Waldron et al, 1999) and is typical for methanogenic environments, due to strong fractionation during methanogenesis (Conrad, 2005;Whiticar, 1999). Therefore, it was frequently found that δ 13 C CO 2 does Fig.…”
Section: Respiration and Methanogenesissupporting
confidence: 78%
“…The isotopic composition of methane in W-V was in accordance with δ 13 C CH 4 reported in other studies, particularly if sedges were present. Values observed in DW-V and DW-D were considerably lighter in isotopic composition than previously reported (Chasar et al, 2000;Lansdown et al, 1992;Popp et al, 1999;Waldron et al, 1999). In the wet treatment W-V, concentrations of methane and total dissolved carbon dioxide reached a steady state and were high enough to sustain measurable emission.…”
Section: Respiration and Methanogenesismentioning
confidence: 49%
See 1 more Smart Citation
“…For example, Waldron et al (1999) reported  13 C values for CH 4 at Ellergower Moss (near New Galloway, UK) substantially different (up to ~10‰) to results later reported by Clymo and Bryant (2008) from similar depths in the same peatland, only 75 m away. Alternatively, given the extreme difference in  13 C values for both the CO 2 and CH 4 components of peat gases, it would only take a small amount of carbon from 1 fraction contaminating the other (during sample processing) to cause a shift in the measured  13 C value.…”
Section: Test Of Sampling and Laboratory Methods On Field Samplesmentioning
confidence: 95%
“…Waldron et al 1999;Steinmann et al 2008). Clymo and Bryant (2008) review some of these studies in the context of their own results, showing general agreement that  13 C values of dissolved CO 2 increase with depth to between +5‰ to +10‰ at depths below several meters.…”
Section: Garnett Et Almentioning
confidence: 99%